Factors associated with anxiety and post-traumatic stress symptomatology during the COVID-19 pandemic in Turkey: A comparison of youths and adults - PERDAHLI FİŞ, NEŞE (My University, 2022)
Objective: The aim of this study was to investigate anxiety and post-traumatic stress symptoms (PTSS) and their possible associated factors among youths, comparing to their older adult counterparts. Patients and Methods: This cross-sectional online study assessed 1493 participants in Turkey. Beck Anxiety Inventory (BAI) and the Post-traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) were used. Results: The Youths (15-24 years) reported to experience more anxiety and PTSS than Adults (25-59 years). There were weak correlations between BAI, PCL-5 scores and duration of recovery and isolation in Adults infected with corona virus disease 19 (COVID-19), but not in Youths. Younger age and lower economic status were common factors for severe anxiety and PTSS, additionally history of mental health needs and loss of an acquaintance due to COVID-19 were specific predictors for anxiety, and having a medical condition was predictor for PTSS in Youths. In Adults, female, lower economic status, having a medical condition, history of mental health needs, and loss of an acquaintance due to COVID-19 were common factors for worsening both PTSS and anxiety, additionally younger age for PTSS and being infected by COVID-19 for anxiety were specific predictors. Conclusion: Pandemic might have a greater impact on mental well-being of youths than adults. Identification of risk factors can shed light on planning, prevention and intervention strategies.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Anxiety; COVID-19; Mental health; Post-traumatic stress disorder (PTSD); Youth; HEALTH; Anxiety; COVID-19; Mental health; Post-traumatic stress disorder (PTSD); Youth